Additional Remarks on the Purification Iconography at the Graeco-Roman Temples of Upper Egypt - موسى، وسام فكري إبراهيم (جامعة قناة السويس - كلية السياحة والفنادق, 2022)
تقدم هذه الورقة دراسة تحليلية مقارنة لمشاهد محددة تم تصويرها على جدران ستة معابد إلهية يونانية ورومانية بصعيد مصر. وهي دندرة وإسنا وإدفو وكوم أمبو وفيلا وكلابشة. في الواقع، باستخدام المفردات الإبداعية المتاحة لهم، قام البطالمة الذين تبعهم الأباطرة الرومان بتزيين جدران تلك المعابد العظيمة بنقوش ومشاهد ذات قيمة رمزية عالية. وهكذا، تركز الدراسة على تصوير حكام البطالمة والرومان وهم يرتدون الملابس والشعارات والرموز المصرية التقليدية، ويتم تطهيرهم عادة كملوك مصريين. هدفت المنهجية المتبعة إلى تحليل هذه المشاهد ومقارنتها بالمشاهد المصرية القديمة المقابلة من حيث الموقع والتفاصيل والشخصيات المصورة. كشفت النتائج عن بعض الابتكارات والتطورات المميزة بالإضافة إلى التأكيد على أن هذا النوع من التمثيل يذهب ليكون أكثر من مجرد تقليد ديني، بل له أحيانا طابع سياسي يبرر القيمة الإيديولوجية والدعاية الهادفة المرتبطة به. يتم تأكيد مكانة الملكية من خلال هذه الروايات المرئية التعبيرية، والتي، بناء على الدراسة الميدانية، غالبا ما تكون في المواقع التي كان للجمهور فيها وصول غير مقيد. كل ذلك بهدف قبولهم كملوك شرعيين وخلفاء للملوك المصريين القدماء. This paper provides an analytical comparative study of specific scenes depicted on the walls of six remarkable Graeco-Roman divine temples of Upper Egypt; Dendera, Esna, Edfu, Kom-Ombo, Phila and Kalabsha. Indeed, employing the creative vocabulary at their disposal, the Ptolemies followed by the Roman Emperors adorned those great temples' walls with reliefs and scenes of high symbolized value. Thus, the study focuses on certain depictions where the Ptolemaic and Roman rulers were portrayed wearing garments, emblems, traditional Egyptian symbols, and being purified typically as Egyptian Kings. The methodology followed aimed at investigating these scenes as well as comparing them with the corresponding ancient Egyptian scenes in terms of location, details, and depicted characters. Findings revealed some distinctive innovations and developments as well as asserting that this kind of representation was more than just a religious tradition, it sometimes has a political character which justifies the purposeful ideological and propaganda value associated to it. The kingship's prestige is confirmed by these expressive visual narratives, which, based on the field study, are often in sites where the public had unfettered access. All with the goal of being accepted as legitimate kings and successors of the ancient Egyptian kings.
Keywords: مصر القديمة -- الأباطرة الرومان -- الروايات التعبيرية -- الشخصيات المصورة -- المفردات الإبداعية